Complications in Patients With Autosomal Dominant Polycystic Kidney Disease Undergoing Ureteroscopy: A Cohort Study. (November 2020) - Kalatharan, Vinusha; Welk, Blayne; Nash, Danielle M.; McArthur, Eric; Slater, Justin; Sarma, Sisira; Pei, York; Garg, Amit X.
Background: Ureteroscopy is a minimally invasive treatment option for upper tract stones. The distorted kidney anatomy in patients with autosomal dominant polycystic kidney disease (ADPKD) may place them at higher risk for ureteroscopic complications. Objective: To compare the 30-day risk of ureteroscopic complications between patients with and without ADPKD. Design: Retrospective cohort study. Setting: Ontario, Canada Patients: Seventy three patients with ADPKD and 81 445 patients without ADPKD who underwent ureteroscopy for upper urinary tract stones between April 1, 2002, and March 1, 2018. Measurements: A 30-day risk of (1) hospital presentation with ureteroscopic complications (which was a composite outcome of either emergency department visit or hospital admission with acute kidney injury, urinary tract infection, or sepsis); (2) all-cause hospital presentation; (3) all-cause hospital admission; and (4) all-cause emergency department visit. Methods: We regressed outcomes on demographic variables, health care use in the prior 1-year, various procedures and comorbidities related to the outcome in the prior 5 years, and prescribed medications filled in the past 120 days using modified Poisson regression to compare the risk ratio (RR) of each outcome between patients with and without ADPKD. Results: The median (interquartile, IQR) age was 44 (38-60 years) in the ADPKD group and 53 (42-64) in the control group. About 40% were women in both groups. The risk of ureteroscopic complications was not significantly different in patients with versus without ADPKD (8.2% vs 4.3%; adjusted RR = 1.5, 95% confidence interval [CI] = 0.7-3.2). Patients with versus without ADPKD were more likely to present to hospital after their procedure (35.6% vs. 20.0%; adjusted RR = 1.6, 95% CI = 1.2-2.2), which included a statistically significant increase in the risk of presenting to the emergency department (32.9% vs. 19.0%; adjusted RR = 1.6, 95% CI = 1.1-2.2) but not hospital admissions (10.9% vs. 5.0%; adjusted RR = 1.8, 95% CI = 0.9-3.4). Limitations: The low numbers of events led to imprecision around the estimates. Conclusion: Patients with ADPKD have a higher risk of return to the hospital within 30 days of ureteroscopy for stone disease. Trial registration: We did not register this study.